Dysphagia and masticatory performance as a mediator of the xerostomia to quality of life relation in the older population - Lu, Ting-Yu; Chen, Jen-Hao; Du, Je-Kang; Lin, Ying-Chun; Ho, Pei-Shan; Lee, Chien-Hung; Hu, Chih-Yang; Huang, Hsiao-Ling (BMC geriatrics, 2020)
The impact of poor oral health on older adults' quality of life is a public health problem. In this study, the mediating effects of dental status, occlusal condition, dysphagia, and masticatory performance on the association between xerostomia and oral health-related quality of life (OHRQoL) were assessed in the older adult population. Stratified cluster sampling was used to recruit 1076 community-dwelling adults aged 65 years and older from Kaohsiung, Taiwan. Community care centers were randomly selected according to their geographic classifications (urban, rural, or mountainous areas). Assessments of dental status and occlusal condition were performed by dentists. Information on demographics, physical function, xerostomia, dysphagia and depression was collected through face-to-face interviews. Masticatory performance was evaluated using color-changeable chewing gum. OHRQoL was measured using the Geriatric Oral Health Assessment Index. Hierarchical regression models were used to assess the relationships between OHRQoL and physical function, dental status and oral function in older adults. Path analysis was used to estimate direct and indirect pathways between xerostomia and OHRQoL. Participants with xerostomia exhibited a 0.20 OHRQoL reduction (p < .001) compared with patients with no xerostomia, and the direct effect accounted for 83.3% of the total effect. Dysphagia and masticatory performance were found to exert significant mediating effects on the association between xerostomia and OHRQoL (βs = 0.20 and - 0.12, respectively; both p < .001; βs = 0.06 and - 0.09, respectively; both p < .05). Moreover, potential mediating effects of the number of functional teeth (βs = - 0.11 and - 0.43, respectively; both p < .001) and occlusal condition (βs = 0.09 and 0.13, respectively; both p < .05) on the relationship between xerostomia and masticatory performance were noted. Dysphagia and masticatory performance may serve as pathways through which xerostomia affects quality of life. Early oral function intervention may be a valuable and actionable target for older adults to maintain quality of life. Our results further suggest that checkup and screening for oral dysfunction are essential to prevent or delay the onset of complications.